2020
DOI: 10.3390/v12121471
|View full text |Cite
|
Sign up to set email alerts
|

Can Coronaviruses Steal Genes from the Host as Evidenced in Western European Hedgehogs by EriCoV Genetic Characterization?

Abstract: Due to their need for living cells, viruses have developed adaptive evolutionary strategies to survive and perpetuate in reservoir hosts that play a crucial role in the ecology of emerging pathogens. Pathogenic and potentially pandemic betacoronaviruses arose in humans in 2002 (SARS-CoV, disappeared in July 2003), 2012 (MERS-CoV, still circulating in Middle East areas), and 2019 (SARS-CoV-2, causing the current global pandemic). As universally recognized, bats host ancestors of the above-mentioned zoonotic vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 42 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…Thirdly, while we agree that the sometimes close associations between hedgehogs and humans could provide a theoretical risk of zoonotic transfers (for hedgehog rehabilitators, hedgehog researchers and those provisioning hedgehogs in their gardens), De Sabato et al 5 estimate that EriCoV originated between 190 and 1447 years ago, and in spite of its long history and high prevalence in hedgehogs, has not yet been recorded to have infected any other host, including humans. Furthermore, our research on methicillin-resistant Staphylococcus aureus (MRSA) indicates that the risk of zoonotic transfers between humans and hedgehogs appears, in practice, to be low 13 .…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Thirdly, while we agree that the sometimes close associations between hedgehogs and humans could provide a theoretical risk of zoonotic transfers (for hedgehog rehabilitators, hedgehog researchers and those provisioning hedgehogs in their gardens), De Sabato et al 5 estimate that EriCoV originated between 190 and 1447 years ago, and in spite of its long history and high prevalence in hedgehogs, has not yet been recorded to have infected any other host, including humans. Furthermore, our research on methicillin-resistant Staphylococcus aureus (MRSA) indicates that the risk of zoonotic transfers between humans and hedgehogs appears, in practice, to be low 13 .…”
mentioning
confidence: 60%
“…Many species of wildlife carry host-specific genetically distinct strains of coronaviruses which cannot infect humans. The coronavirus previously detected in hedgehogs is called EriCoV [2][3][4][5] . The prevalence of EriCoV in hedgehogs appears to be rather high, ranging from 10.8% in Great Britain 3 to 50% in France 6 to 58.3% in Italy 2 , and 58.9% in Germany 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, a number of studies have contributed to widen our knowledge of CoV distribution and genetic diversity. Whereas bats have remained the main focus of field surveys, and probably represent the major natural reservoir of alphaCoVs and betaCoVs, other small mammals such as rodents and shrews are increasingly recognized to host a large variety of coronaviruses (Annan et al, 2013;Anthony et al, 2017;Corman et al, 2015;Corman, Ithete, et al, 2014;Corman, Kallies, et al, 2014;De Sabato et al, 2020;Hu et al, 2017;Lam et al, 2020;Latinne et al, 2020;Lau et al, 2015;Li et al, 2021;Tao et al, 2017;Tsoleridis et al, 2016Tsoleridis et al, , 2019Wang et al, 2015Wang et al, , 2020Wang, Fu et al, 2017;Wang, Lin et al, 2017;Yang et al, 2014;Zhou et al, 2021). Also, wild birds are known to host a substantial diversity of deltaCoVs and gammaCoVs (Wille & Holmes, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, it has become more than clear that potentially zoonotic betacoronaviruses can represent massive public health threats, such as those related to Middle East respiratory syndrome coronavirus (MERS-CoV), or more recently and globally with severe acute respiratory syndrome coronavirus (SARS-CoV-2). Recent findings of MERS-related CoVs in hedgehogs from Germany [39], France [24], and Great Britain [40] suggest that E. europaeus represents a wild reservoir of betacoronaviruses named as Erinaceus CoVs (EriCoVs) [12,41]. In 2020, a study that analysed virological and epidemiological data of COVID-19 outbreaks in Wuhan, China, comparing it with SARS-2002 and MERS-2012 outbreaks concluded that, among other findings, the responsible agent was genetically close to SARS-related viruses isolated from bats.…”
Section: Bacteriamentioning
confidence: 99%